Asymmetric introgression between the M and S forms of the malaria vector, Anopheles gambiae, maintains divergence despite extensive hybridisation - Marsden, Clare D. (2011)
The suggestion that genetic divergence can arise and/or be maintained in the face of gene flow, has been contentious since first proposed. This controversy and a rarity of good examples has limited our understanding of this process. Partially reproductively isolated taxa have been highlighted as offering unique opportunities for identifying the mechanisms underlying divergence with gene flow. The African malaria vector, Anopheles gambiae s.s., is widely regarded as consisting of two sympatric forms, thought by many to represent incipient species, the M and S molecular forms. However, there has been much debate about the extent of reproductive isolation between M and S, with one view positing that divergence may have arisen and is being maintained in the presence of gene flow, and the other proposing a more advanced speciation process with little realised gene flow due to low hybrid fitness. These hypotheses have been difficult to address because hybrids are typically rare (<1%). Here, we assess samples from an area of high hybridisation and demonstrate that hybrids are fit and responsible for extensive introgression. Nonetheless, we show that strong divergent selection at a subset of loci combined with highly asymmetric introgression has enabled M and S to remain genetically differentiated despite extensive gene flow. We propose the extent of reproductive isolation between M and S varies across West Africa resulting in a “geographic mosaic of reproductive isolation”; a finding which adds further complexity to our understanding of divergence in this taxon and which has considerable implications for transgenic control strategies.